Sterılızatıon And Dısınfectıon In Clınıcal Orthodontıcs - İlter Uzel; Bülent Haydar (Galenos Yayinevi, 1989)
Recently a great deal of attention has been devoted to the spread of hepatitis b and aids viruses and the high risk of contamination of these viruses during the dental operations has mode orthodontists more aware of the recessity of sterilization and dezenfection. This article discusses the methods of sterilization and disinfection. Avoidance of corrosion of instruments and the use of a ultrasonic cleaner to avoid contamination has been explained. In the conclusion the measures that the orthodontist has to take in order to protect himself is discussed.